The Effect of Emotional Freedom Technique (Eft) Therapy on Anxiety Levels In Pre Mothers Sectio Caesarea At Bpm Bengkulu City - Agustina, Fatma; Elly, Nur; Dahrizal, Dahrizal; Asmawati, Asmawati; Husni, Husni; Yovalwan, Tahratul; Rahmadani, Wahyudi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Background: Anxiety in mothers before giving birth reaches 18-70% from 5.263.057 which can have an impact on delaying surgery, increasing hospitalization days, and can cause postpartum depression.  Objective: The purpose of this study was to determine the effect of emotional freedom technique (EFT) therapy on the level of anxiety in pre-sectio caesarea mothers at BPM Bengkulu City. Method: The research design used was a quasi-experiment design with a pretest-posttest design with a control group. The study sample was pregnant women aged ?35 weeks with indications of SC (displacement, fetal/pelvic disproportion, previous SC history, twins). The number of samples in this study was 34 respondents (17 respondents in each group). The sampling technique used in this research is total sampling. The instrument used is the Anxiety Assessment Scale Pregnant for women in Labour (AASPWL). Data analysis was performed using the Wilcoxon test and the Mann-Whitney test with a confidence value of 0.05. Result: The results showed that after being given the EFT intervention there was a difference in the level of anxiety scores in sectio caesarea mothers with a mean difference of around 3.24 (p-value 0.000). Conclusion: The EFT intervention is a benefit for lower anxiety in mothers before delivery by SC.